NUTRITIONAL AND PSYCHOLOGICAL IMPACT OF DIABETES ON DIABETICS: CASE STUDY IN THE TAMALE TEACHING HOSPITAL - GHANA - Kubuga, Clement Kubreziga; Mensah, Michael; Osei, Gilbert; Osei, Solomon Ofori; Abugre, Dominic (European Scientific Journal, ESJ, 2013)
This study sought to assess the role of diabetes on food intake and the psychological impact of living with diabetes among diabetics in the Tamale Teaching Hospital. A self structured questionnaire was administered among 97 sampled diabetic respondents at the diabetic clinic in the Tamale Teaching Hospital. The studies found out that diabetes does have a role to play on the food intake of diabetics in the Hospital. It was also found out that generally a healthy meal plan for the diabetic respondents is the same as a healthy diet for anyone. The outstanding difference in the food intake of the diabetics in the hospital was their no or limited intake of sugar which sometimes was substituted with honey. Mean individual dietary diversity score of 5.37 was obtained reflecting that the dietary diversity score for diabetics did not meet the optimum level (≥ 6). Male and Female diabetic respondents had mean FCS of 22.95 and 22.12 respectively which falls within the borderline food consumption category. On the psychological impact of diabetes, this studies found out that all diabetic respondents had the risk of post traumatic stress disorder (PTSD); about four out of every six diabetic respondents had 75% chance of being diagnosed with post traumatic stress disorder as a result of living with diabetes while one out of every six diabetic repondents had the greatest chance (above 75%) of being diagnosed with PTSD.